Impact of collection methods on semen quality, fertility, and hatchability in nunukan chickens - Fatmarisch, Novemia; Indana, Khoiru; Manullang, Jusyenti; Raharja, I M.U.; Mbincar, Bryta; Ardhani, Fikri (Fakultas Peternakan Universitas Papua, 2025)
This study aims to evaluate the fertility and hatchability of Nunukan chickens responding to the rooster semen collected using the dorso-abdominal massage method and a collection tube by presenting a teaser. A total of 20 male Nunukan chickens were divided into two treatment groups, in healthy condition, aged 12-36 months, body weight 2.5-3.4 kg, and housed individually (35x45x60 cm3); the semen was collected every three days. Semen characteristics evaluated macroscopically included color, odor, consistency, volume, and pH; microscopically included sperm concentration, mass motility, progressive individual motility, total sperm per ejaculate, viability, abnormality, and sperm quality factor (SQF); furthermore, the artificial insemination technique was used to evaluate the effect of sperm quality on fertility and hatchability. Both methods showed no difference in macroscopic parameters; color, odor, consistency, and pH, and microscopic parameters (p>0.05); concentration, viability, abnormality, mass motility, and progressive individual motility. While semen volume, total sperm per ejaculate, and SQF showed significant differences (p<0.05). However, the fertility and hatchability rates are not significantly different (p>0.05). Despite the high quantitative qualities of rooster semen obtained with collection tubes and female teasers, Nunukan chickens' fertility and hatchability did not differ significantly (p>0.05) from other semen collection methods. Keywords: collection method; fertility; hatchability, semen, quality